The Impact of Antibiotics Administration on Mortality for Time in Sepsis and Septic Shock Patients including Possible Reasons for Delayed Administration in Malaysia - Ann L. Arulappen; Monica Danial; Ling Wei Ng; Jui Chang Teoh (MDPI AG, 2022)
The 2017 Surviving Sepsis Campaign guidelines endorse a focus on the rapidity of treatment once sepsis has been identified, with a strong recommendation for the administration of antimicrobial drugs within one hour; however, the quality of the supporting evidence is evaluated as moderate. This study was conducted for six months prospectively at a single center in an intensive care unit (ICU) from March 2020 to August 2020. All the patients, regardless of their age and gender, admitted into ICU who had their first episode of sepsis or septic shock concomitantly started on a broad-spectrum antibiotic given intravenously. For patients who had multiple episodes of sepsis throughout the study period, data from the very first episode of the sepsis were included in this study. Of all the 78 patients, only 38 (48.7%) received the antibiotics prescribed within an hour. The compliance rate as per the Surviving Sepsis Campaign was only 51.3%, which accounted for 40 patients. The overall survival rate was 60.3%. This study revealed that delayed antibiotics administration (more than an hour) significantly affects mortality.